THE URGENCY OF MARKET SIZE EVALUATION AND PRODUCT DIVERSIFICATION: Evidence from the Brick Industries in Bireuen Regency - Hismendi, Hismendi; Jayanti, Ery; Saputra, Ismayli; Mukhlis, Mukhlis (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The brick industry in Bireuen Regency has grown and developed as a home-based business. The average lifespan of these businesses is more than 3 years. The fixed cost burden borne is relatively low where the industrial location area is owned by the company. This shows that the brick business is relatively easy if it want to entry the market, especially in Bireuen. The purpose of this study is to highlight market size and product diversification as important aspects to be reviewed in an effort to develop the brick industry leading to a more profitable business venture in Bireuen Regency. This research was conducted using experimental-based primary data obtained from 199 business units in the Peusangan, Kota Juang, and Jeumpa sub-districts as production center areas. The methods of data and analysis with using the approaches; (i) Total Addressable Market (TAM), (ii) Serviceable Available Market (SAM), and (iii) Share of Market (SOM). Research shows that each brick business controls less than 2 percent of the market share. To expand the market size to the Regency’s Pidie Jaya and Bener Meriah, and even to Aceh Tengah and Pidie Regencies, it is necessary to diversify brick products by offering a variety of sizes and textures and adding additives. Thus, the brick industry has a competitive advantage over other products, such as lightweight bricks or concrete blocks.